Selected parameters of anaerobic capacity and body tissue components in handball players from the premier league team - Krawczyk, K. (Journal of Kinesiology and Exercise Sciences, 2015)
Study aim. Review of literature related to handball reveals that modern handball performed at the highest level of competition is dominated by short-term, 5-20 second sequences of anaerobic efforts. Given the above data and lack of scientific reports describing the level of anaerobic capacity in handball players representing a high sports level, it was considered appropriate to investigate the efficiency of this field of capacity in the men`s premier league team. The aim of the study was to assess the relative mechanical work (J/kg) and maximal power (W/kg) obtained in the Wingate test, and to measure tissue components (BMI, FAT%, TBW%). Study design. Subjects: 16 handball players from the premier league team. The average age of subjects = 25.33 ± 7.05 years, mean body height = 192.40 ± 7.18 cm, mean body mass = 98.31 ± 12.82 kg. Anaerobic capacity assessment was carried out in accordance with the Wingate - 30 s testing procedure, using the Monark 824E bicycle ergometer, and the MCE v. 5.0 computer program. Measurement of body tissue components were made using the Tanita SC330 body composition analyzer. Results. The average maximum power was - 11.15 ± 0.80 W/kg, average work - 253.88 ± 16.93 J/kg, average time of attaining power - 4.83 ± 081s, time of maintaining power - 3.06 ± 1,08 s. The average BMI was 26.45 ± 1.91; FAT% -12.92 ± 3.27; TBW% -59.02 ± 2.43. Conclusions. In the process of training handball at a high competitive level, more attention should be paid to the development of anaerobic endurance by increasing the share of interval-type loads.